2019
DOI: 10.3928/00989134-20190709-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Acupoint Massage on Blood Glucose Level and Quality of Life in Older Adults With Type 2 Diabetes Mellitus: A Randomized Controlled Trial

Abstract: iabetes is becoming a threat to global health (International Diabetes Federation, 2017). In China, type 2 diabetes mellitus (T2DM) accounts for approximately 87% to 91% of all types of diabetes, and the incidence of young patients is on the rise, which will be a heavy economic burden on patients and the country (Gao, 2006; Wang et al., 2017). Despite the regimen of oral medication and/or insulin for T2DM, successful blood glucose control relies more on patient selfmanagement, including diet, exercise, health e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…Conventional massage consists of regular and rhythmic movements of the therapist's hands on body tissues, including nerves and muscles, to achieve certain goals. Several studies [3][4][5] have shown that massage improves glucose and lipid metabolism disorders by regulating muscle, inflammatory factors, and pancreatic islet function. Compared with routine massage, abdominal massage is not only easy to perform, but can also improve gastrointestinal function and lipid metabolism [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional massage consists of regular and rhythmic movements of the therapist's hands on body tissues, including nerves and muscles, to achieve certain goals. Several studies [3][4][5] have shown that massage improves glucose and lipid metabolism disorders by regulating muscle, inflammatory factors, and pancreatic islet function. Compared with routine massage, abdominal massage is not only easy to perform, but can also improve gastrointestinal function and lipid metabolism [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers recommended more extensive and diverse participant samples in future digital health interventions [ 150 , 171 , 173 , 247 ] and consideration of low compliance rates within sample size calculations [ 173 ]. They believed that providing participants with an explanation of the potential benefits and utility of the technology may also enhance study participation [ 173 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with a study of self-acupoint massage on blood glucose levels in older adults with type 2 diabetes mellitus, which showed that there were no significant changes in FBG and 2-hour postprandial blood glucose levels between the massage and control groups, while there was a significant difference in HbA1c levels. [70] Bleeding at the stimulated site during acupuncture therapy and slight contusion of the skin tissue during massage therapy are common adverse reactions. However, only 2 of the 59 studies reported adverse effects.…”
Section: Discussionmentioning
confidence: 99%